Analisis Hukum Peran Kepala Desa Sebagai Mediator Perdamaian Desa dalam Menyelesaikan Sengketa Rumah Tangga (Studi pada Kantor Kepala Desa Deli Muda Hulu) - Pertiwi, Dian; Sahbudi, Sahbudi; Muhlizar, Muhlizar (Jurnal Ilmiah Penegakan Hukum, 2025)
As the lowest level of government, the village plays a crucial role in maintaining order and resolving conflicts within the community. One of the Village Head's obligations, as stipulated in Law Number 6 of 2014 in conjunction with Law Number 3 of 2024, is to resolve disputes arising within the village, including domestic disputes. In Deli Muda Hulu Village, the high divorce rate reported by the Seirampah Religious Court indicates that domestic disputes are a serious issue. This underscores the importance of the Village Head's role as a peace mediator before disputes escalate to litigation. The study found that the Village Head of Deli Muda Hulu played a significant role as a communication facilitator and informal mediator, prioritizing deliberation and family values. Conflict resolution through village mediation can prevent escalation of disputes, maintain family honor, and preserve local community values. However, several weaknesses exist, both from the perspective of the litigants—such as lack of adherence to agreements and high emotional factors—and from the perspective of the village, such as limited legal authority, insufficient mediation capacity, and minimal official documentation. Village mediation agreements have the legal force of a private civil agreement, but lack enforceable power. Therefore, this study recommends the need to improve the capacity of village heads, more systematic documentation of mediation results, and the establishment of Legal Aid Posts (Posbakum) in villages. Posbakum is expected to strengthen legal aspects, provide legal education, and assist communities to ensure that mediation outcomes are fairer, more effective, and in accordance with the principles of legal protection.